2015
DOI: 10.1016/j.molmet.2015.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of adropin on glucose tolerance and substrate utilization in diet-induced obese mice with insulin resistance

Abstract: ObjectiveThe peptide hormone adropin regulates fuel selection preferences in skeletal muscle under fed and fasted conditions. Here, we investigated whether adropin treatment can ameliorate the dysregulation of fuel substrate metabolism, and improve aspects of glucose homeostasis in diet-induced obesity (DIO) with insulin resistance.MethodsDIO C57BL/6 mice maintained on a 60% kcal fat diet received five intraperitoneal (i.p.) injections of the bioactive peptide adropin34-76 (450 nmol/kg/i.p.). Following treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
188
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 150 publications
(210 citation statements)
references
References 86 publications
11
188
0
Order By: Relevance
“…However, against these data Gao et al (48) tried ADR treatment of diet-induced obesity with IR mice and found ADR treatment enhanced glucose tolerance, ameliorates IR and promotes preferential use of carbohydrate over fat in fuel selection and indicated a negative relationship between ADR level and high blood glucose level and IR; thus supporting the findings of the current study. Thereafter, Tuna et al (15) experimentally detected high serum ADR levels among animals received calorie-restricted diet, while was significantly lower among animals maintained on normal calorie intake, thus supporting the inverse correlation between serum ADR levels and calorie intake.…”
Section: Discussion:-supporting
confidence: 86%
“…However, against these data Gao et al (48) tried ADR treatment of diet-induced obesity with IR mice and found ADR treatment enhanced glucose tolerance, ameliorates IR and promotes preferential use of carbohydrate over fat in fuel selection and indicated a negative relationship between ADR level and high blood glucose level and IR; thus supporting the findings of the current study. Thereafter, Tuna et al (15) experimentally detected high serum ADR levels among animals received calorie-restricted diet, while was significantly lower among animals maintained on normal calorie intake, thus supporting the inverse correlation between serum ADR levels and calorie intake.…”
Section: Discussion:-supporting
confidence: 86%
“…Moreover, increased release of adropin is related to the fed state and increased glucose oxidation by pyruvate dehydrogenase (PDH) complex activation. Furthermore, adropin inhibits carnitine palmitoyltransferase-1B (CPT1B), which reduces fatty acid oxidation (FAO) in muscles [17]. According to recent studies, it can be speculated that higher concentration of adropin in women with GDM is one of the multiple adaptive responses on adverse glucose metabolism during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…For example, adropin, a relatively newly discovered peptide hormone, is synthesized and secreted primarily by the liver but is also found in the heart and brain [9]. Dietary macronutrients stimulate adropin secretion and systemic injections of adropin to obese mice have been shown to improve glucose tolerance, skeletal muscle insulin sensitivity and promote weight loss [9, 29]. The role of adropin in the pathophysiology of feline obesity and diabetes is unknown.…”
Section: Introductionmentioning
confidence: 99%